Pembangunan Intake Spam Instalasi Pengelolaan Air (IPA) Longalo di Bulango Utara, Bone Bolango, Gorontalo - Anwar, Rustam; Yasin, Irfan; Faisal, Moh; Rahmat, Asep (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
All living things are very dependent on water. Its existence and function are the source of life for all creatures on earth. This research article studies how to construct intakes to support water supply to optimal levels of processing before distribution activities to the community take place. The community's need for clean water is very necessary according to their daily needs. The problem is that if adequate intake development and construction is not carried out, then a shortage of distribution to the community occurs at any time. This is the reason why the local government is obliged to build an intake that functions as an addition to the capacity of clean water in processing IPA for the community. This research applies a survey method with the ultimate goal of developing an intake development system in Longalo, Bone Bolango. This designed system practically does not require permits for environmental protection and management considering its position on a relatively small scale to support the IPA function in Longalo, Bone Bolango.